Peran Perawat dalam Mengatasi Diabetes Distress - Hasanah, Laila; Yulia, Yulia; Edison, Chiyar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to guide nurses in therapeutic communication with patients with diabetes distress. The method used in this writing is a literature review through several databases, namely Pubmed, ClinicalKey, Proquest, and Science Direct. The research results show that diabetes distress is a common thing experienced by patients with diabetes mellitus. In conclusion, treating diabetes distress is part of comprehensive diabetes management. Keywords: Diabetes Distress, Nurse's Role